The practice of the faith used as a therapeutic treatment in the patient pain and recovery process: in the nurse's vision - Leite, Weseleny Souza (Revista Coleta Científica, 2018)
Article to demonstrate that the practice of faith practiced by the patient during therapeutic treatment helps in the process of pain and recovery in the view of the nurse demonstrating the benefits of faith to the patients. Methodology: This research consists of an exploratory and descriptive study, carried out through an integrative review of the literature, the data were collected through searches in virtual databases: Scielo, BVS and LILACS. Results: Results showed that the practice of faith brings benefit to the patient during the therapeutic treatment, and demonstrated how the nurse can perceive this practice so that it can contribute to the development of strategies for the care of the patient during the care provided by the nursing team. Conclusion: Patients and family members who practice faith in different ways had benefits during the therapeutic treatment by the nurse's perception. It is recommended that nurses in providing care have sensitivity to support the patient exposed to stressful situations, who have neutrality, respecting the belief or lack of it in each one, avoiding that discomfort is generated.